Determinants of Financial Intermediation: Empirical Evidence from Cameroonian Commercial Banks - Giscard, Moutie; Roland, Ntomane; MESSOMO, Elle Serge (Archives of Business Research, 2022)
Current financial intermediation theory is build on the notion that intermediaries serve to reduce transaction costs and informational asymmetries. As developments in information technology, deregulation, deepening of financial markets tend to reduce transaction costs and informational asymmetries, financial intermediation theory shall come to the conclusion that intermediation becomes useless. It also conflicts with the continuing and increasing economic importance of financial intermediaries. Cameroonian economic policy from 1988 restructured the financial sector towards a greater Financial Intermediation (FI). This article seeks to identify the determining factors of FI in Cameroon in relation with the practitioner’s view of financial intermediation as a value-creating economic process. In order to attain this principal objective, we use secondary data for the period 1977 to 2016. This analysis is done with three multiple linear regressions which emphasise on FI’s determinants in respect to FI’s components. The study shows that deposit interest rate positively affects FI through credit and monetary mass and negatively through intermediation margin. The expected inflation rate positively influences FI via intermediation margin and negatively through credit and monetary mass. The interest rate on loans and minimum reserves are directly linked to the components of FI (monetary mass and intermediation margin). This could be explained by the restructuring of the banking system, bank overliquidity, MFE’s instability and poor growth environment. Thus banks might consolidate their management system in order to ensure their credibility as well as their continuity.